Pengembangan Pariwisata Berbasis Collaborative Governance di Pahlawan Street Center (PSC) Kota Madiun - Isni Wahidiyah Susanto; Asrifia Ridwan (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
Tourist destinations have prospects for regional progress and regional income generation. Pahlawan Street Center (PSC) in Madiun City is a popular destination, despite its previous condition being a slum area and vulnerable to flooding. This research describes the development of collaborative governance-based tourism in the Madiun City PSC using descriptive qualitative case study methods developed using primary and secondary data findings. The results of the research show that Madiun City PSC tourism can develop inseparable from the role of the Mayor of Maidi government in collaborating with various partners, especially groups of UMKM actors and Regional Apparatus Organizations. The development of Madiun City PSC tourism has had a positive impact on both the community and the government. For the community, the existence of new tourist attractions can help the economy, while for the government, apart from increasing Regional Original Income, on the other hand, it also adds the essence of new tourist interest in Madiun City.